2011
DOI: 10.1210/en.2010-1079
|View full text |Cite
|
Sign up to set email alerts
|

Calcitropic Hormones and IGF-I Are Influenced by Dietary Protein

Abstract: Elderly men and women with protein deficiencies have low levels of circulating IGF-I, and it is likely this contributes to reduced bone formation and increased bone resorption. We hypothesized that calcitropic hormones are involved in this effect and are affected by dietary protein. We therefore investigated the influence of a low-protein diet on the PTH-1,25-dihydroxyvitamin D3 [1,25(OH)₂D₃] axis and IGF-I in rats, using pamidronate to block resorption that normally contributes to mineral homeostasis. We fed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
10
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 44 publications
3
10
1
Order By: Relevance
“…Whereas previous studies have essentially focused on the impact of dietary protein level on bone geometry, mineral content, and midshaft bone strength (4 -6, 36), to the best of our knowledge, no studies have examined the effects of protein deficiency on trabecular bone microarchitecture during growth. Moreover, in agreement with the present results, we previously demonstrated that a low-protein diet impairs trabecular bone microarchitecture in mature rats (10,37).…”
Section: Impact Of Reduced Protein Intakes On Bone and Hormonal Statusupporting
confidence: 93%
See 1 more Smart Citation
“…Whereas previous studies have essentially focused on the impact of dietary protein level on bone geometry, mineral content, and midshaft bone strength (4 -6, 36), to the best of our knowledge, no studies have examined the effects of protein deficiency on trabecular bone microarchitecture during growth. Moreover, in agreement with the present results, we previously demonstrated that a low-protein diet impairs trabecular bone microarchitecture in mature rats (10,37).…”
Section: Impact Of Reduced Protein Intakes On Bone and Hormonal Statusupporting
confidence: 93%
“…However, little is known about their interaction on skeletal growth and the related endocrine regulation. Besides, we know that dietary protein may modulate the secretion and action of calciotropic hormones, (10) and interestingly, the response to calcium supplementation in prepubertal children appears to be influenced by the spontaneous protein intake (23). In this study, we hypothesized that a lowCa/Pi diet may magnify the harmful effect of a low-protein diet on bone growth.…”
mentioning
confidence: 99%
“…Certain studies have also suggested that carboxylated osteocalcin has no effect on mineralization (3)(4)(5). Others have provided evidence that carboxylated osteocalcin may play a role in bone turnover (6,7). Moreover, serum concentrations of osteocalcin have been established as the main marker of bone turnover (8).…”
Section: Introductionmentioning
confidence: 99%
“…However, it was shown that decreased dietary protein intake caused massive changes in mineral homoeostasis and vitamin D metabolism in young goats (4,5) ; this being reflected by reduced levels of blood Ca, 1,25-dihydroxyvitamin D 3 (calcitriol) and insulin-like growth factor 1 (IGF1). Protein restriction was also shown to have an impact on Ca homoeostasis, IGF1 and vitamin D metabolism in monogastric species like humans and rats (6)(7)(8) .…”
mentioning
confidence: 99%